ДЕТЕРМІНАНТИ РОЗВИТКУ БАНКІВСЬКО- СТРАХОВОЇ МОДЕЛІ КОМПЛЕКСНОГО ОБСЛУГОВУВАННЯ СПОЖИВАЧІВ ФІНАНСОВИХ ПОСЛУГ - Ткаченко, Наталія Володимирівна (Науковий журнал «Світ фінансів», 2017)
Ткаченко Н. В. Детермінанти розвитку банківсько-страхової моделі комплексного обслуговування споживачів фінансових послуг. Обґрунтовано відмінності в змістовному навантаженні термінів “банківське страхування” та “страхування банківських ризиків”, окреслено основні напрямки страхування банківських ризиків. Здійснено історичний екскурс використання поняття bancassurance. Сформульовано переваги банкострахування, зокрема в контексті об’єднання іпотечного кредитування зі страхуванням життя позичальника. Ткаченко Н. В. Детерминанты развития банковско-страховой модели комплексного обслуживания потребителей финансовых услуг. Обоснованы различия в содержательной нагрузке терминов “банковское страхование” и “страхование банковских рисков”, обозначены основные направления страхования банковских рисков. Осуществлен исторический экскурс использованиия понятия bancassurance. Сформулированы преимущества банкострахования, в частности в контексте объединения ипотечного кредитования со страхованием жизни заемщика. Tkachenko N. Determinants of development of bank-insurance model of comprehensive service of financial services consumers. Introduction. Now the development of financial intermediation is observed not only as deepening competition between banks and non-bank private institutions but also mutual cooperation, which contributes to expand the range of services offered by such financial institutions. Banking and insurance segments of the Ukrainian economy is under active development and transformation that generates a lot of interest to the study of models of cooperation. Purpose. The aim of the article is to clarify the economic content of the concept of “bancassurance” to study the differences between the “bancassurance” and the “insurance of bank risks” and to determine the specifics of bancassurance. Results. The economic content of the concept of “bancassurance” is clarified. The differences in the content load of the terms “bancassurance” and “insurance of bank risks” are justified. An analysis of scientific approaches and our own considerations provides a reason to determine bankassurance as the distribution strategy of insurance products, which provides for their distribution through the bank’s branch network. It can be provided using a combination of different types of banking and insurance activities. As a result of implementation of bancassurance’s concept the nature of interaction of banks and insurance companies is changing, borders between banking and insurance products are disappearing, trends for consolidation on finance market are increasing. The main directions of insurance banking risks identified. Historical background of bancassurance concept is implemented. Advantages of bancassurance in the context of the association of mortgage lending life insurance borrower formulated. Conclusion. The interpretation of the term “bank insurance” can be approached from two perspectives. From an institutional point of view, bancassurance is a way of organizing the process of cooperation between banks and insurance companies. From a functional point of view, bancassurance is revealed through the organization and setting up cross-selling of banking and insurance products, that is, through a single point of sales, mainly through the network of bank branches and bank branches. The main advantages of bancassurance are the maximum benefit from the coordination of sales, the combination of banking and insurance products, the development of programs to attract new customers and the improving of service system of customer base overall. In other words, bancassurance is a leading component of the financial services offered through the mechanism of interaction between banks and insurance companies.